Trends in monkeypox research: A sixty year bibliometric analysis - Shuaibu Adeiza; Abdulmalik Shuaibu (Microbes and Infectious Diseases, 2022)
Aim:  The purpose of the study was to identify common descriptors and publication hotspots that may form reference themes for future monkey pox research. Method: Bibliometric analysis of monkeypox related studies between 1962 and 2022 was carried out to ascertain and describe this body of literature. Results and conclusion: A total of 1,134 documents were analysed for bibliometric indicators. The studies had 3,478 authors, an average of 5.72 co-authors per publication and a 3.73 author collaboration index. Annual scientific production peaked in 2004 (5.5%) and 2020 (5.3%). Monkeypox research accumulated 128 grants, 68 policy documents, 9 clinical trials, and 50 patents. The United States placed first in terms of the number of documents and citations, followed by Germany with 73, United Kingdom with 53, Russia and the Democratic Republic of the Congo (DRC) with 34 documents each. The DRC and Nigeria had the most documents among African countries. Text mining showed researchers have put their efforts into studies related to infectious disease ‘epidemiology’: the ‘emergence’, ‘Case diagnosis and ‘surveillance’ of ‘outbreaks’. The top keywords were ‘monkeypox’ (570 times), ‘monkeypox virus’ (411 times), ‘poxviridae infections’ (332 times), ‘small pox’ (266 times), ‘orthopox virus’ (248 times), ‘vaccinia virus’ (203 times), and ‘disease outbreaks’ (179 times). The most cited treatment related noun phrases were ‘tecovirimat’ (brand name Tembexa), ‘Cidofovir’/ ‘CMX001’ (Brincidofovir), ‘ACAM2000’ (imvanex vaccine) and ‘Vaccinia’ Immune Globulin (‘VIG’). This result will serve as a foundation for future research, guiding decision-making in monkeypox research and therapy.